The Microneurosurgical Training Model for Intrinsic and Extrinsic Brain Tumor Surgery Using Polyurethane Foam and Fresh Cadaveric Cow Brain: An Experimental Study - Altun, Adnan (World Neurosurg X, 2019)
OBJECTIVE: To evaluate the feasibility of an experimentally designed brain tumor model consisting of polyurethane foam and fresh cadaveric cow brain for the surgical training of the technique for tumor ablation. METHODS: A laboratory-training model was created for microneurosurgical intervention of intrinsic brain tumor ablation covering microdissection of the brain tissue and opening of the pia mater, dissection and separation of the sulcal and cisternal structures, and dissection and removal of the tumor tissue. The left front parietal lobe was used as the area of interest for this experimental study. One-centimeter cube polyurethane foam was injected 2-cm deep inside the brain tissue using a plastic injection tube. After 5 minutes, the model was ready to use under the operating microscope for dissection, separation, and removal of the tumor tissue. The compatibility of the training model also was evaluated as poor, acceptable, and perfect. RESULTS: Ten stripped fresh cadaveric cow brains were used in this experimental feasibility study. The compatibility of the model was evaluated as poor, acceptable, and perfect in 1, 6, and 3 subjects, respectively. CONCLUSIONS: In intrinsic brain tumor ablation, surgical manipulations of sulcal, cisternal, and fissural dissection must be undertaken while preserving vital neural and vascular structures. We believe that our model holds promise in developing the technical skills of neurosurgeons in training.